Pengaruh Harga, Content Marketing, dan Online Consumer Review Terhadap Keputusan Pembelian Di Pengguna Tiktok Shop (Studi Kasus pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Nina Bilqis Maharani; Nurhajati Nurhajati; Muhammad Ridwan Basalamah (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The purpose of this study is to discover and analyze the pricing, content marketing, and online consumer reviews that influence purchasing decisions for TikTok store users. The sample for this research was users of the 2019 batch of tiktok shop management students from the Faculty of Business and Economics, Islamic University of Malang, with 85 respondents. The independent variables consist of the variables of price, content marketing and online consumer reviews. Meanwhile, the dependent variable of this study is the purchase decision variable measured using multiple linear regression analysis using SPSS 25. The result of the study is that there is a simultaneous influence of price, content marketing and customer reviews online consumers on purchasing decisions on tiktok shop users of students at the University of Malang Islam Faculty of Economics and Business. Meanwhile, the partial effect only occurs in the price variable on purchasing decisions, while the content marketing and online consumer reviews variables have no partial effect on purchasing decisions. Keywords: Online Store, Price, Content Marketing, Online Consumer Reviews, Purchase Decision